Colégio Normal São José, Ibiá/MG (1937-1969): Entre os cânones religiosos, morais e educattivos voltados para a profissionalização docente - Souza, Sirlene Cristina de (2024)
This doctoral thesis is located in the line of research of History and Historiography of Education, falls within the sub-area of History of School Institutions and focuses on the analysis of the History of the Teaching Profession, Gender and Education. The main theme of the scientific research work is the history of Colégio Normal São José in Ibiá, Minas Gerais, founded by the Religious Missionaries of Our Lady of Sorrows (RMNSD), on March 19, 1937. Regarding the research hypothesis, it is believed that the founding of the College was due to the influence of the local elite, with the support of political and religious powers to install a college, in the municipality, that would meet the demand for women's training, due to the lack of a qualified teaching staff that could meet the interests of these women same segments. This educational institution operated as a boarding school, day school and semi-boarding school for women and its trajectory in the first three decades of activities summarizes its participation in the process of disseminating Catholic morality and the teaching professionalization of girls/women in the municipality of Ibiá and in the Triângulo Mineiro and Alto Paranaíba region. Thus, the general objective of the research is to investigate the participation of the RMNSD Congregation by means of trajectory of Colégio Normal São José in the process of teaching professionalization, based on the analysis of teaching and student practices, the knowledge and values conveyed inside and outside the school routine, during the period between 1937 and 1969. In 1937, the school was founded, in subsequent years until 1969, the effective activity of the RMNSD Congregation in Ibiá became evident, and from that date onwards, lay teachers entered, including teachers from the male gender and the progressive deactivation of Patronato São José. In this sense, some problems become clear during the investigation: What are the characteristics, purposes and dimensions of the historical trajectory of Colégio Normal São José founded by the Congregation of Missionary Religious Women of Our Lady das Dores, in the municipality of Ibiá? What are the educational, moral and religious canons of Colégio Normal São José, aimed at the training of primary teachers, in the historical context of 1937 to 1969? What are its implications for the projection of these women in society? What are the content and methodological legal prescriptions for achieving this training ideal? What is the identity of the research subjects on the teaching professionalization process in terms of teaching profile and student profile? So, in the dialogue with the theoretical framework and the inventoried sources, the following categories of analysis emerge: gender, teaching professionalization, Catholic renewal, religious congregation, political elite, social classes, pedagogy of example. This is research from an analytical perspective on the sources, raised through the articulation of synchronic and diachronic information between the singular and the universal, and the relationships of reciprocity and determination between the spheres: national, regional and local. The investigation unfolded as oral, bibliographic and documentary research, using quantitative and qualitative data obtained through consultation of documentary and iconographic sources and interviews carried out with former students and teachers of the College; using primary and secondary sources subjected to explanatory analyzes of dialectical historical materialism. Therefore, the research presents the thesis that Colégio Normal São José, through the action of the Congregation of the RMNSD, through religious, moral and educational canons, contributed to the promotion of women in the public space, through the process of teacher training and professionalization. The greater possibility of participation in public space, through leaving home for school, presented itself as a process of resistance, opening the doors of the job market to those who wanted more than to educate their own children, to become primary teachers and professionals respected. The research results indicate that Colégio Normal São José managed to remove a significant number of women from Ibia society and the Triângulo Mineiro/Alto Paranaíba region from anonymity, elevating them to occupy a position in the public space. Educated women sought to break with the hegemony of patriarchal society, creating, through teacher training and professionalization, fields of action and autonomy in the public space. It is concluded that Colégio Normal São José contributed to the maintenance of traditional moral values, but also to intellectual training, with the development of skills and competencies necessary for normalists to exercise their profession. So being a primary teacher gave many of those girls/women greater autonomy, freedom of movement and decision-making power, resulting from the exercise of an intellectual and paid activity.